Study on Local Inflammatory Reactions and Other Parameters During Subcutaneous Mistletoe Application in HIV-positive Patients and HIV-negative Subjects Over a Period of 18 Weeks - Stoss, Matthias; Wely, Madelon van; Musielsky, Herbert; Gorter, Robert W (Arzneimittelforschung, 1999)
Subcutaneous injections of fermented and unfermented aqueous extracts of Viscum album L. result in a local inflammatory reaction at the injection site. In this trial, the symptoms associated with this local reaction were investigated. Furthermore the occurrence of local reactions was tried to correlat with an increase in CD3/25- and CD8/38-positive lymphocyte counts, with eosinophilic granulocyte numbers, and with the formation of mistletoe lectin antibodies. Included in the trial were 30 HIV-antibody-positive patients and 17 healthy non-smokers, aged 24-51 years. The CD4 cell count in the HIV-negative subjects was > compared with in the HIV-positive patients. All study participants had a Karnofsky score 70. The trial subjects were observed over a period of 18 weeks.With escalation of the dose of a fermented and unfermented extract of Viscum album L. (Iscador® Qu Spezial and Viscum album QuFrF), there was an increase in local reactions. Erythema at the injection site was the most frequently reported symptom. Between the doses and the symptoms induration, swelling and pruritus were marked correlations. Effects of the application of mistletoe extracts on the immune system were demonstrated by an increase in CD3/25-positive lymphocyte counts and antibodies against mistletoe-lectins. There were no changes in eosinophilic granulocytes or CD8/38-positive lymphocyte populations.For evaluation of the therapeutic applications of mistletoe extracts in HIV-positive patients it is advisable to assess primarily activation of CD3-positive lymphocytes and the patient response on the basis of the local reaction. The local inflammatory reaction at the injection site is desirable and well tolerated if the reaction is smaller than 5 cm in diameter.
Keywords: CD3/25- and CD8/38-positive lymphocytes; Iscador®; Mistletoe lectin, antibodies; Viscum album L., aqueous extract, HIV-negative; subjects, HIV-positive patients, local inflammation reaction